PENGARUH NILAI TUKAR, PDB, DAN PEMBIAYAAN BANK SYARIAH TERHADAP EKSPOR KOPI DI INDONESIA - Ginting, Siti Nurhasanah Br; Harahap, Muhammad Ikhsan; Tambunan, Khairina (Jurnal Manajemen Terapan dan Keuangan, 2024)
This research aims to determine the influence of exchange rate variables, Gross Domestic Product (GDP) and Sharia Financing on coffee exports in Indonesia. The method used in this research is a quantitative method, using timeseries (secondary) data with data collection techniques using documentation studies, namely by collecting data on Exports, GDP, Exchange Rates and Financing distributed by Sharia Banking obtained from the website of the Central Bureau of Statistics (BPS). ), Bank Indonesia (BI), Financial Services Authority (OJK) and ICO (International Coffee Organization). The data was then analyzed using the VECM (Vector Error Correction Model) method using Eviews 10 software. This shows that financing has an effect on the exchange rate which is significant in the long term but has no significant effect in the short term. Apart from that, based on the results of the impulse response analysis, it caused shocks but did not cause too much volatility in Indonesian coffee exports. The exchange rate has no effect on GDP, and GDP has no effect on financing. Then, based on the results of the variance decomposition analysis, it shows that the value of financing plays the biggest role in the exchange rate of Indonesian coffee exports. And it has a significant effect in the long term but does not have a significant effect in the short term on the volatility of Indonesian coffee exports.